Investigating strategic responses of SMEs during COVID-19 pandemic: A cognitive appraisal perspective - Dario Miocevic (BRQ Business Research Quarterly, 2023)
In this study, we investigate the response intentions of small- and medium-sized enterprises (SMEs) during the recent economic crisis initiated by the COVID-19 pandemic. We draw on the cognitive appraisal theory and investigate how an SME's level of proactivity triggers top managers' emotional reactions, which in the end shapes an SME's response strategies (investment vs divestment). To test our assumptions, we use survey data from 155 top managers of Croatian SMEs operating in business-to-business industries. We find that an SME's proactivity positively (negatively) influences the emergence of positive (negative) emotions. Also, we find that top managers charged with positive (negative) emotions are more prone to engage in investment (divestment) as a response to economic crisis. Furthermore, through the broaden-and-build perspective we reveal the mediating effect of emotions on the relationship between proactivity and response intentions as well as the mediating effect of performance expectations on the link between emotions and response intentions.
Keywords: M10; M19; 650; Economic crisis; cognitive appraisal; proactivity; emotions; response strategies